Analisis Unsur Ekstrinsik Pada Novel “Layla Dan Majnun” Karya Nizami Ganjavi - Laraswati Laraswati; Muhammad Septian (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This study analyzes the extrinsic elements in Layla and Majnun, a masterpiece by Nizami Ganjavi, to explore the cultural, moral, and social contexts influencing the story. Using a library research method, the study examines the author's background, the values within the story, and the social conditions of 12th-century Persia. The findings reveal that the novel is deeply rooted in Nizami's spiritual and intellectual environment, reflecting themes of loyalty, sacrifice, and divine love influenced by Sufism. Furthermore, the social conflicts portrayed in the story highlight the tension between individual desires and societal norms, making it a timeless reflection of human experience. This research contributes to understanding how extrinsic elements enrich literary works and suggests further comparative studies to explore global literary traditions.